117k views
0 votes
Help someone!!!?!!?!?!?!

Help someone!!!?!!?!?!?!-example-1

2 Answers

6 votes

Explanation:

Given,

b^2 - 7b - 4

Substitute b = 3 in equation ,we get

=> (4)^2 - 7(4) - 4

=> 16 - 28 - 4

=> 16 - 32

=> - 16. Ans.

User Marc Guerin
by
5.0k points
7 votes

Answer:

When we have b=3, we can replace 3 instead of b in the expression.

⇒b²-7b-4

Replacing b with 3

⇒(3)²-7(3)-4

As 3² is 3×3=9 and 7×3=21 we get

9-21-4

⇒-12-4

⇒-16

Thus, -16 is the final answer when b=3

User Juvian
by
5.4k points